O poder da palavra em sua esfera conceitual: pontes para a autonomia da pessoa em múltiplas dimensões - Laquimia, Tatiane Patricia (2012)
This Final Work of Master essentially a literature review aimed to reflect on "the power of the word in its conceptual sphere" and for that, understand it as a "bridge that can mediate a person's autonomy" or several of them when a group. To this end, organized into chapters, which show through subtle "multiple dimensions", namely: anthropological, religious and educational, the structuring of these bridges/ways in the search for the right to say the word. Preceding the first chapter has a brief history feedback by trying to show the relevance of the power of the word in the development of mankind to find himself in the mold as it is known today. This feedback pervaded by the slave, the woman, the child, the person with special needs, the black, the Indian, the poor, or, for those who really had long denied their right to speak. The anthropological dimension itself brought discussions about the "ethics of care staff, collective and planetary", where it was found that the right to say the word itself is directly related to posture and decisive humanitarian behavior first personal and then collective. And this attitude showed that consequently is reflected in global welfare. The educational dimension dealt with the "theories of the formation and its multidisciplinary perspective multireferential through management to leadership and spirituality, and the interfaces of practice teaching: mediating learning and learning to say the word." In this, it was observed that the features of the new teacher training and the current way of understanding and conduct education possible in too self-awareness and awareness of this new generation of citizens who know certainly require and safely use their property and right to speak. Finally, the religious dimension presented "approach to faith." This chapter emphasizes the autonomy of the word entirely when it comes to personal spiritual relationship, however, in order to respect and participation with the traditions and religious cultures. Together these dimensions or structural bridges, can enable the awareness, awareness, motivation and finally to (transform)action of these people / citizens in favor of his right to position themselves and make themselves see, hear and therefore comply with front society in its different spheres, for if understood and expressed, those delivering the personal word autonomous. Thus, Freire says that, saying his word is not a privilege or right of some men, but of them all. Speaking only of the right to speak is still a soft stance, as to have an opinion and action is a duty of every citizen conscious and committed to their surroundings. Therefore, in this context (and paraphrasing Clarice Lispector) means and it is believed that the strength of 'my' word has power of control over the transformation of 'my' world.